2016
DOI: 10.1158/1535-7163.mct-16-0095
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Enhances the Efficacy of Irinotecan through miR-627–Mediated Inhibition of Intratumoral Drug Metabolism

Abstract: Cytochrome P450 enzyme CYP3A4 is an important drug metabolizing enzyme and high levels of tumoral expression of CYP3A4 are linked to drug resistance. We investigated the function of vitamin D-regulated miR-627 in intratumoral CYP3A4 suppression and its role in enhancing the efficacy of chemotherapy. We found that miR-627 targets CYP3A4 and suppresses CYP3A4 expression in colon cancer cell lines. Furthermore, calcitriol (the active form of vitamin D) suppressed CYP3A4 expression by activating miR-627. As a resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Although it seems that MK1775 monotherapy could achieve an anticancer effect in p53 mutant colonic cancer cells, the dosage for treatment is still a challenge, as the toxicity of agents targeting the cell cycle checkpoint is big problem. Combination with other chemotherapy drugs is a better choice as a first-line chemotherapy regime in metastatic colonic cancer (25), and a number of studies are seeking the proper strategy to increase the sensitivity of cancer cells to the cytotoxicity effect (26)(27)(28). In the present study MK1775 was demonstrated to increase the sensitivity of cells to the effect of irinotecan both in HT29 and SW480, and resulting in increased γ-H2AX and cleaved-caspase 3.…”
Section: Discussionmentioning
confidence: 52%
“…Although it seems that MK1775 monotherapy could achieve an anticancer effect in p53 mutant colonic cancer cells, the dosage for treatment is still a challenge, as the toxicity of agents targeting the cell cycle checkpoint is big problem. Combination with other chemotherapy drugs is a better choice as a first-line chemotherapy regime in metastatic colonic cancer (25), and a number of studies are seeking the proper strategy to increase the sensitivity of cancer cells to the cytotoxicity effect (26)(27)(28). In the present study MK1775 was demonstrated to increase the sensitivity of cells to the effect of irinotecan both in HT29 and SW480, and resulting in increased γ-H2AX and cleaved-caspase 3.…”
Section: Discussionmentioning
confidence: 52%
“…No published data exists so far on the interaction between irinotecan and SATB2. Irinotecan is inactivated by cytochrome P450 3A4 (CYP3A4), whose activity can be reduced by miRNA [25]. Since miRNAs are known targets of SATB2, an indirect effect on irinotecan efficacy can be surmised.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated a tumour suppressive role of miR‐627‐5p in HCC. miR‐627‐5p functions as a tumour suppressor in CRC by targeting JMJD1A and CYP3A4 . Meanwhile, miR‐627‐5p exerts the tumour suppressive role in GBM via attenuating CDK6 and SOX‐2 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐671‐5p and miR‐204 mediate hypoxia‐induced HCC progression via regulating vasodilator stimulated phosphoprotein (VASP) and tuftelin 1 (TUFT1), respectively . MiR‐627‐5p has been previously recognized as a tumour suppressor in colorectal cancer (CRC) and glioblastoma multiforme (GBM) . Vitamin D‐induced miR‐627‐5p inhibits the proliferation of CRC cells by repressing Jumonji domain containing 1A (JMJD1A) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation